Silvery tunnel - Mazlan, Norida (Universiti Putra Malaysia Press, 2013)
Human has been living together with millions of insects species for as long as the world exists. Thus the relationship of human and insect was formed in many ways. One of the forms is the work arts. Insect provide inspirations and creativity to humans. One of these creative insects is the citrus leaf miner (Phyllocnistis citrella Stainton).